KCNE1 D85N polymorphism - a sex-specific modifier in type 1 long QT syndrome? - Marjamaa Annukka; Lahtinen Annukka M; Swan Heikki; Kontula Kimmo (BMC, 2011)
Abstract Background Long QT syndrome (LQTS) is an inherited ion channel disorder manifesting with prolongation of the cardiac repolarization phase and severe ventricular arrhythmias. The common KCNE1 D85N potassium channel variant prolongs QT interval by inhibiting IKs (KCNQ1) and IKr (KCNH2) currents and is therefore a suitable candidate for a modifier gene in LQTS. Methods We studied the effect of D85N on age-, sex-, and heart rate-adjusted QT-interval duration by linear regression in LQTS patients carrying the Finnish founder mutations KCNQ1 G589D (n = 492), KCNQ1 IVS7-2A>G (n = 66), KCNH2 L552S (n = 73), and KCNH2 R176W (n = 88). We also investigated the association between D85N and clinical variables reflecting the severity of the disease. Results D85N was associated with a QT prolongation by 26 ms (SE 8.6, p = 0.003) in males with KCNQ1 G589D (n = 213), but not in females with G589D (n = 279). In linear regression, the interaction between D85N genotype and sex was significant (p = 0.028). Within the KCNQ1 G589D mutation group, KCNE1 D85N carriers were more often probands of the family (p = 0.042) and were more likely to use beta blocker medication (p = 0.010) than non-carriers. The number of D85N carriers in other founder mutation groups was too small to assess its effects. Conclusions We propose that KCNE1 D85N is a sex-specific QT-interval modifier in type 1 LQTS and may also associate with increased severity of disease. Our data warrant additional studies on the role of KCNE1 D85N in other genetically homogeneous groups of LQTS patients.